OCCURRENCE OF NEUTRALIZING ANTIBODIES AGAINST BVDV-1 AND BVDV-2 IN CATTLE HERDS FROM MINAS GERAIS AND SÃO PAULO STATES, BRAZIL / Ocorrência de anticorpos neutralizantes contra o BVDV-1 e o BVDV-2 em rebanhos bovinos de Minas Gerais e São Paulo, Brasil. - DIAS, F. C.; ALEXANDRINO, B.; MEDEIROS, A. S. R.; DIAS, E. C.; BUZINARO, M. G.; SAMARA, S. I. (Ars Veterinaria, 2011)
A ocorrência de anticorpos neutralizantes contra os genótipos do vírus da diarréia viral bovina (BVDV-1 e BVDV-2) foi determinada pelo teste de virusneutralização (VN) em amostras de soro sangüíneo provenientes de 26 rebanhos bovinos não vacinados contra o BVDV, localizados nos Estados de Minas Gerais e São Paulo, Brasil. Foram analisadas 10 amostras por rebanho, sendo cinco de bovinos adultos e cinco de bovinos com idade entre 6 e 12 meses. Do total de 260 amostras analisadas, 102 (39,2%) reagiram ao BVDV, das quais 81 (31,1%) foram reagentes tanto ao BVDV-1 quanto ao BVDV-2, sete (2,7%) reagiram apenas ao BVDV-1 e 14 (5,4%) reagiram apenas ao BVDV-2. Com exceção de dois rebanhos, nos demais foram detectados pelo menos um animal reagente ao BVDV, entretanto, foram detectados animais reagentes apenas ao BVDV-2 em um deles. Em seis rebanhos foram detectados anticorpos neutralizantes nos bovinos da faixa etária de 6 a 12 meses, sendo, portanto, indicativos da infecção recente pelo vírus e também sugestivos da provável presença da fonte de infecção no rebanho. Os dados obtidos mostraram a ocorrência de anticorpos neutralizantes contra os genótipos do BVDV em rebanhos bovinos localizados nos Estados analisados, mas os resultados apresentaram diferenças no número de bovinos reagentes ao BVDV-1 e ao BVDV-2, ressaltando assim a necessidade da utilização de estirpes de cada genótipo nos testes de VN para o diagnóstico sorológico do BVDV. SUMMARY The occurrence of neutralizing antibodies against bovine viral diarrhea virus genotypes (BVDV-1 and BVDV-2) has been confirmed by virus neutralization test (VN) in samples of blood serum from 26 cattle herds which were not BVDV vaccinated, located in the states of Minas Gerais and São Paulo, Brazil. Ten blood samples were collected from each herd, five samples from 6 to 12-month-old calves and five samples from adult bovines. Of the total samples analyzed, 102 (39.2%) were reactive to BVDV, more specifically, 81 (31.1%) were reactive to BVDV-1 and BVDV-2, seven (2.7%) were reactive to BVDV-1 only and 14 (5.4%) were reactive to BVDV-2 only. Except for two herds, in all others at least one animal was detected reactive to BVDV, however, one of them was reactive to BVDV-2 only. In six herds, neutralizing antibodies were detected in blood serum from 6 to 12-month-old calves. Therefore, were indicative of recent BVDV infection and also suggested the likely presence of an infection source in the herd. The results showed the occurrence of neutralizing antibodies against BVDV genotypes in cattle herds located in the states analyzed, but these same results demonstrated the differences in the number of bovines reactive for BVDV-1 and BVDV-2, thus demonstrating the need to use strains from each genotype in VN tests for serological diagnosis of BVDV.